2017
DOI: 10.4085/1062-6050-52.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Plantar-Massage Techniques on Postural Control in Those With Chronic Ankle Instability

Abstract: In those with CAI, single 5-minute sessions of traditional plantar massage, self-administered massage, and sensory brush massage each resulted in comparable static postural-control improvements. The results also provide empirical evidence suggesting that the mechanism for the postural-control improvements is the stimulation of the plantar cutaneous receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…The unsupervised sessions for the FIRE intervention will consist of single-limb balance, triceps surae stretching, supination and pronation resistance band, and intrinsic foot muscle exercises. Additionally, plantar massage will be self-administered by rolling the plantar surface of the foot on a textured massage ball on the ground [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The unsupervised sessions for the FIRE intervention will consist of single-limb balance, triceps surae stretching, supination and pronation resistance band, and intrinsic foot muscle exercises. Additionally, plantar massage will be self-administered by rolling the plantar surface of the foot on a textured massage ball on the ground [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…These mechanoreceptors can change by myofascial release. Wikstrom et al [31] have reported that myofascial release by manual, ball, or sensory brush in individuals with chronic ankle instability positively affects static postural-control, and have hypothesized the involvement of mechanoreceptors for these effects. However, this is only a hypothesis and there is not enough scientific evidence to support the changes in mechanoreceptors after myofascial release.…”
Section: Discussionmentioning
confidence: 99%
“…The plantar surface of the foot is a part of the sensorimotor system, which consists of plantar receptors of the foot, ankle joint, and musculotendinous receptors [ 19 ]. In some studies, it has been described that the stimulation of sensory receptors may improve sensorimotor function [ 19 , 20 , 21 , 45 ]. LeClaire et al [ 20 ] have reported immediate effects of plantar foot massage on the improvement of postural control in individuals with chronic ankle instability.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these therapies resulted in comparable static postural-control improvements. The researchers suggested that stimulation of the plantar cutaneous receptors may be the underlying mechanism of postural-control improvement following the plantar massage [ 45 ]. McKeon et al [ 19 ] also evaluated the efficacy of the plantar message, triceps surae stretching, and ankle joint mobilisations on the objective and subjective outcome measures regarding sensorimotor dysfunctions and clinical disablement in patients with chronic ankle instability.…”
Section: Discussionmentioning
confidence: 99%